Sekolah Kebijakan: Model Pelatihan Partisipatif Penyusunan Regulasi Responsif Gender Di Satuan Pendidikan Menengah - Wira Anshori, M.; Destemi Elsi, Sutri; Suci Pratiwi, Cholillah; Jeane Putri, Revi; Hanafi Ahmad, Zakly; Abdi Muhammad, Hatta (Jurnal Pengabdian kepada Masyarakat Desa (JPMD), 2025)
This community service program, titled “Policy School: Formulating Gender-Responsive Policies in SMAN 11 Kota Jambi”, was conducted as part of the Tri Dharma of Higher Education. The activity aimed to enhance the understanding and capacity of teachers and school administrators in integrating gender perspectives into educational policies and practices. The method used was participatory training, including focus group discussions, lectures, and collaborative policy drafting sessions. The participants were guided to identify gender issues within the school environment and to formulate responsive policy recommendations. The results indicated an increased awareness of gender equality values and improved competence among participants in designing school regulations that promote inclusivity. This program also produced a draft of gender-responsive school policy as an output. In conclusion, the activity successfully strengthened institutional capacity in promoting gender mainstreaming in education at the school level.